Menstrual hygiene among the undergraduate medical college students in Churachandpur Medical College, Manipur, North Eastern state of India - Devi, Okram Sarda; Vashum, Melody; Laishram, Guddi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Menstruation is very important monthly event in the life of adolescent. Educating girls and women about menstrual hygiene is vital to break taboos, promote health, and empower them to manage their periods hygienically and confidently. For this knowing the awareness and practices and prevalence menstruation related health issue are also important. Methods: The study is a cross-sectional observational study done on all undergraduate’s female medical graduates of Churachandpur medical college (Imphal Campus) Manipur. from May 15th, 2024 to June 15th, 2024. Results: In the current study, it is noted that 100% of participants have menstrual related health issues and dysmenorrhea was the commonest among the menstrual related health issues. And a huge number of students did not receive treatment for the menstrual related health issues. Less than 50% of students have accessibility to separate toilet. And 55% have restriction during menstrual cycle. Conclusions: It is noted from the current study that there are numerous problems regarding menstrual hygiene that need to be address. So, providing more accessible menstrual clinics is crucial.